Promoting healthy eating nutrition at public school: an experience report in the Week of Education for Life (WEL) (Research, Society and Development, 2020)
Formal education in the public educational environment has become the focus of research and experiments today, with curricular components and their approaches criticized for their cast and traditional model. The Education for Life Week, is a proposal of the federal government with the purpose of assigning curricular components in the format of science fair and greater interaction of the school public, thus, the scholarship holders of the Institutional Program of Teaching Initiation Scholarship (PIBID / CAPES) of the biology subproject, allocated at the Federal University of Itajubá (UNIFEI) helped the thematic execution of the event in a public school in the city of Itajubá, located in the State of Minas Gerais. The objective of this article is the experience report of the theme “healthy eating” that occurred in the place, which had a great adhesion to the school and community public, with the objective of discussing about the awareness of the act of eating well, by the method of playful circuit. As a result, a high adhesion of the school community, and dialogical action.